Identification and characterization of the Cassava core-clock gene Early Flowering 4 - Adeyemo, O. Sarah; Kolmos, E; Tohme, Joseph M.; Chavarriaga Aguirre, Paul; Fregene, Martin A.; Davis, S.J. (Springer, 2011)
The angiosperm circadian clock has been well established from molecular-genetic studies in a temperate plant model. Conservation of clock function is less explored in plants from the tropics. Cassava (Manihot esculenta) is a staple crop grown in the tropics that has been of limited research interest, and more generally, research on photoperiod and clock genes has been sparse. EARLY FLOWERING 4 (AtELF4) of the temperate plant Arabidopsis thaliana (Arabidopsis) has been reported to be required for photoperiod perception and circadian function. Here, we describe our start to identify circadian and photoperiod genes in cassava with an account on the characterization of its ELF4 gene (MeELF4). After isolating MeELF4, a phylogenetic study was conducted and it was found to cluster within the ELF4 subclade of the ELF4/EFL super-family. Similar to studies in temperate plants, MeELF4 was shown to be an evening-expressed gene in cassava. This collectively suggested to us that MeELF4 could be a functional ortholog of AtELF4. To test this, complementation studies of MeELF4 were performed in the Arabidopsis elf4 mutant. Hypocotyl-length measurements and flowering-time analysis were performed. MeELF4-complementation transgenics in the elf4 background were restored to the wild-type growth habit, suggesting a total rescue of photoperiodic perception. To expand on the molecular role of MeELF4 in the resulting transgenic-complementation lines, the CCA1 and CCR2 promoter-luciferase markers where respectively introduced and bioluminescence-imaging experiments revealed a restoration of circadian-regulated gene expression. The collective results showed that the cassava gene MeELF4 is a functional clock ortholog of AtELF4.